Screening in Graphene: Response to External Static Electric Field and an Image-Potential Problem - Vyacheslav M. Silkin; Eugene Kogan; Godfrey Gumbs (Nanomaterials, 2021)
We present a detailed first-principles investigation of the response of a free-standing graphene sheet to an external perpendicular static electric field E. The charge density distribution in the vicinity of the graphene monolayer that is caused by E was determined using the pseudopotential density-functional theory approach. Different geometries were considered. The centroid of this extra density induced by an external electric field was determined as <semantics>zim</semantics> = 1.048 Å at vanishing E, and its dependence on E has been obtained. The thus determined <semantics>zim</semantics> was employed to construct the hybrid one-electron potential which generates a new set of energies for the image-potential states.